Rama do obrazu w służbie kształtowania wnętrza - Wantuch-Jarkiewicz, Katarzyna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2010)
Picture frame, as others elements of interior design in various époques played more or less auxiliary role towards such elements as the architecture or furniture. So not only the theme was important, but also the surrounding, in which the painting was set.